Dynamics and functional relevance of ribonucleoproteic membrane-less organelles - Boccaccio, Graciela Lidia (2020)
The dynamic formation of stress granules (SGs), processing bodies (PBs) and related RNA membrane-less organelles, regulates diverse cellular processes, including the coordination of functionally linked messengers, and the translational regulation at the synapse among others. The formation of these cellular bodies is governed by liquid-liquid phase separation (LLPS) processes, and their dysregulation may provoke pathogenic aggregation. LLPS in vitro depends on the thermal diffusion of macromolecules, which is limited inside cells, where the condensation and dissolution of membrane-less organelles (MLOs) would be helped by energy-driven processes. We found that the active transport by the retrograde motor dynein helps SG assembly, whereas the anterograde motor kinesin mediates SG dissolution, and a tug of war between these molecular motors allows transient SG formation. As in the case of PBs, SGs contain repressed mRNAs but are not required for their silencing, and the contribution of SGs to the protective response triggered upon stress remains elusive. In addition to SGs and PBs, several RNA granules and related MLOs are present in neurons. We found that distinct subsets of PBs and additional RNA bodies located at dendrites and synapses respond selectively to specific synaptic stimuli, which promote their rapid assembly or disassembly, thus controlling the release of bound mRNAs. This modulates the local transcriptome and allows fine-tuning of the translation at the post-synapse. More recently, we focused on Smaug MLOs. Smaug orthologs are highly conserved in the animal kingdom and recognize a wide variety of stem-loops termed Smaug Recognition Elements (SREs), which are present in a large number of mRNAs including nuclear transcripts that encode mitochondrial enzymes. We performed time lapse confocal microscopy and found that Smaug1 MLOs are highly motile and frequently contact mitochondria, speculatively coordinating the transport and/or the translation of nuclear-encoded mRNAs at the mitochondrial periphery.